Joint motions affecting the energy transfer to the club during the golf swing - Takagi, T. (ISBS Proceedings Archive (Michigan), 2018)
This study identified the effect of joint motions on the force power and segment torque power acting on the golf club, and investigated contributions of proximal joint motions to energy transfer to the club during the golf swing. Sixteen skilled golfers performed swings with the driver. Their 3D kinematic data were collected using an optical motion capture system. The wrist joint force power and club segment torque power were decomposed into powers relating to 1) velocity of the center of the gravity of pelvis, and angular velocities of 2) pelvis, 3) lumber joint, 4) shoulder joint, and 5) wrist joint. The powers associated with the pelvis angular velocity were the main components of the power generation at the wrist joint. The powers associated with the pelvis and proximal joint angular velocities reached their peak simultaneously. These findings indicate that synchronised timing of the peak powers might represent an efficient strategy to maximise the energy transfer to the club during the golf swing.